Perancangan Desain Karakter dalam Komik Strip Instagram untuk Edukasi Penyakit Asam Lambung pada Remaja - Erica Paramita Rahmadhanty; Aninditya Daniar; Bayu Setiawan (FKIP, Universitas Palangka Raya, 2026)
Acid reflux disease is one of the most common diseases experienced by the public, especially in adolescents. The causes of this disease are generally due to psychological conditions, diet, sleep patterns, lifestyle and bacterial infections. However, the high number of cases of this disease is not accompanied by awareness and knowledge of the dangers and changes in a better lifestyle. In order to attract interest in knowing about acid reflux disease and invite to change a better lifestyle, education given in another and interesting form is an option. That's why the design of Instagram comic strips with the aim of education about stomach acid disease is carried out. In a comic, character is an important element needed so that the story and message delivery can be done effectively. This design uses descriptive qualitative and descriptive quantitative research methods to analyze data from interviews, questionnaires and literature. The stage is then continued by making design concepts and design results. From this design, it is hoped that the community, especially teenagers, can be more aware and more effective in conveying messages.